(untitled) (Sukuna Journal, 2026)
This study inspects the significance of pronunciation for Nepali secondary-level learners of English by recognizing major linguistic and pedagogical components that affect their spoken accessibility and communicative competence. Meanwhile, pronunciation plays a central role in effective oral communication, and research focusing specifically on secondary school learners in Nepal, which emphasizes classroom environments, teacher expertise, and suprasegmental features, remains limited. Acquiring a qualitative research design, the study focuses on discovering both language-related and classroom-based barriers that delay the development of accurate pronunciation. Data were collected through structured questionnaires and in-depth inquiry to secondary level students, where the analysis was guided by self-determination theory. The findings specify that learners’ pronunciation difficulties stem from a combination of strong first language influence, insufficient exposure to authentic spoken English, unpredictable instructional practices, and unacceptable classroom conditions. Moreover, inadequacy in teachers’ training further hinders learners’ ability to develop clear and confident speech. This study concludes that improving pronunciation results in Nepali secondary requires directed professional development for mentors, improved connection to spoken English input, and classroom practices that promote frequent, low fear speaking opportunities. Focusing on these fields can contribute to improving pronunciation, enhancing learner confidence, and making English language learning more effective overall.